Current account determinants in ASEAN 6 - Novi Ariyani; Fajar Wahyu Priyanto; Lilis Yuliati (Journal of Economics, Business, and Accountancy Ventura, 2018)
This study aims to analyze the factors that influence the export activity in the ASEAN region countries such as Indonesia, Singapore, Thailand, Malaysia, Philippines and Vietnam during 2001 - 2016 by using annual data. The factors that influence gross domestic product (GDP), interest rate, foreign direct investment (FDI) and exchange rate. The method used in the research is panel Vector Error Correlation Model (PVECM). The results show that Gross Domestic Product (GDP) negatively affects the current account in the short term. The interest rate variable negatively affects the current account in the long term. The Foreign Direct Investment (FDI) variable negatively affects the current account in the long term. Furthermore, the exchange rate variable negatively affects the current account in the long term.